Knowing the Mississippi - Mona M. Smith, Mark Muller, Mark Gorman, Patrick Hamilton, Richard M. Mizelle, Jr. (Open Rivers, 2015)

(untitled)
We asked a diverse group of river people to respond to the prompt “How did you come to know the Mississippi River? What does it mean, to you, to know the Mississippi River?” We present below a few of the responses, in no particular order.